2000
DOI: 10.1016/s0893-133x(99)00161-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Levels of cAMP-dependent Protein Kinase Regulatory Subunits in Platelets from Schizophrenic Patients

Abstract: Abnormalities in the cAMP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
(26 reference statements)
1
17
1
2
Order By: Relevance
“…Thus, activation of PKA in striatum could partially be involved in mediating extrapyramidal side effect by HAL, whereas CLOZ, which has opposite effects on PKA in this and other brain areas, may not only be preventing extrapyramidal side effect but may be associated with its antipsychotic properties. Interestingly, a recent study suggests that the expression of RI and RII subunits of PKA are decreased in the platelets of schizophrenia subjects (Tardito et al, 2000), raising the possibility that schizophrenia may be related to PKA activation and that CLOZ may alleviate the symptoms by deactivating PKA.…”
Section: Antipsychotics and Protein Kinase A 207mentioning
confidence: 99%
“…Thus, activation of PKA in striatum could partially be involved in mediating extrapyramidal side effect by HAL, whereas CLOZ, which has opposite effects on PKA in this and other brain areas, may not only be preventing extrapyramidal side effect but may be associated with its antipsychotic properties. Interestingly, a recent study suggests that the expression of RI and RII subunits of PKA are decreased in the platelets of schizophrenia subjects (Tardito et al, 2000), raising the possibility that schizophrenia may be related to PKA activation and that CLOZ may alleviate the symptoms by deactivating PKA.…”
Section: Antipsychotics and Protein Kinase A 207mentioning
confidence: 99%
“…A post-mortem study found reduced PKA regulatory subunits in schizophrenia patients (Tardito et al, 2000), indicating that PKA signalling may be related to the pathophysiology of schizophrenia. In vivo studies have suggested that PKA signalling may be involved in the clinical effects of antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…Results of many studies support the finding that alterations in PKA and some of its substrates are associated with various psychiatric disorders, including anxiety, depression, obsessive compulsive and bipolar disorders, schizophrenia, and panic disorder [172,173,174,175,176,177]. CNC is a rare multiple endocrine neoplasia syndrome that was first described by Dr. Carney (Mayo Clinic, USA) in 1985 as a complex of myxomas (cardiac, skin, cutaneous), spotty skin pigmentation, and endocrine overactivity [178].…”
Section: Clinical and Pharmacokinetic Studies Of The Pka Pathwaymentioning
confidence: 67%